Sosialisasi Pengenalan Fauna Endemik yang Langka di Indonesia untuk Meningkatkan Pemahaman Peserta Didik Dalam Menjaga Kelestarian Keanekaragaman Hayati di SMP Negeri 9 Langsa - Tanjung, Rizkan; Sri Jayanthi; Silvia Wardania; Sahna Maulana Sitakar; Muliani Tiana Sari; Arini Shinta Zahara; Dwi Putri Sinabariba; Siti Zubaida; Enca Pepayosa; Rauzatul Jannah MZ; Khairunnisa (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Indonesia is known as one of the countries with a wealth of endemic flora and fauna. However, threats to the survival of endemic species such as habitat destruction, poaching, and climate change are increasing. Conservation efforts depend not only on government policies, but also on public awareness, especially the younger generation. This research aims to increase the understanding of students at SMP Negeri 9 Langsa about the importance of preserving rare endemic fauna through a socialization program. The evaluation design of the socialization activities carried out is by using research instruments in the form of pre-test and post-test questions. The results of the activity showed a significant increase in the level of understanding of students about the importance of endemic fauna conservation, measured through pre-test and post-test. In addition, this activity also succeeded in fostering students' sense of responsibility for environmental conservation. Based on the results of the pre-test and post-test t tests, it was found that there was a significant effect between the pre-test and post-test results. The t value of 15.688, df of 24, and Sig (2-tailed) value < 0.001 (p < 0.05) indicate a significant difference between the pre-test and post-test results. Therefore, after the proposed hypothesis is tested against the data, it can be concluded that the level of understanding of students in the introduction of rare endemic fauna in Indonesia has a significant effect or has increased.